PENGARUH STRUKTUR ORGANISASI, KEPEMIMPINAN, MOTIVASI, TERHADAP KINERJA ADVOKASI LEGAL OFFICER (Studi Kasus PT. AP1) - Ajiari TN, Turah; Supriyadi, Edy; D, Derriawan (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
This study examine the phenomenon of the influence of Advocacy Performance carried out by Legal Officer of PT AP I in carrying out Legal Advocacy in its company. The purpose of this study are to analyze the influence of Organizational Structure, Leadership, and Motivation on Advocacy Performance. This study uses quantitative methods because this study meets the elements of a particular population or sample, the existence of data collection activities using research instruments, with the aim of the research is to test the hypotheses that have been set. The results of this study indicate that Organizational Structure and Leadership have a significant influence on Advocacy Performance, coupled with the existence of Motivation as an intermediary which provides a significant increase in Advocacy Performance at PT AP I.